Synthesis, tribology, electro-tribology and mechanical performance of ti2alc and ti3alc2 max phases thin films - Quispe Dominguez, Roger (Pontificia Universidad Católica del Perú, 2023)
This thesis investigates the synthesis, mechanical properties, tribological and electro-tribological behavior of Ti2AlC and Ti3AlC2 MAX phases in the form of thin films. The thin films were obtained by deposition of a multilayer system of Titanium (Ti) - Aluminum (Al) - Carbon (C) and subsequent thermal annealing in a vacuum and controlled atmosphere. The Ti-Al-C multilayer system was deposited by magnetron sputtering on silicon substrates with a SiO2 and SixNy double-layer diffusion barrier. The stoichiometric of the film was controlled through the thickness of the individual monolayers. To obtain a 500 nm thick film, the Ti-Al-C sequence was repeated 22 times with individual thicknesses of 14, 6 and 3.5 nm, respectively. The experimental results show that the Ti2AlC phase is formed at a temperature of 700°C, while the Ti3AlC2 phase is formed at 950°C. The structural properties of the thin films were characterized by X-ray diffraction, Raman microscopy and glow discharge optical emission spectroscopy (GD-OES). The hardness of the thin films was analyzed by nanoindentation tests, obtaining hardness values of 11.6 and 5.3 GPa for Ti2AlC and Ti3AlC2, respectively. The tribological behavior of the thin films was analyzed under dry sliding conditions using a ball-on-flat reciprocating tribometer. The counter body consisted of AISI 52100 steel balls of 3 mm diameter. The friction coefficients obtained were in the range of 0.21 - 0.2 and 0.6 - 0.91 for the Ti2AlC and Ti3AlC2 thin films, respectively. The Ti2AlC phase has a better tribological performance, which can be attributed to its smaller grain size, lower surface roughness and higher hardness compared to the Ti3AlC2 phase. The electrical resistivity of the thin films was 0.73 and 0.45 μΩ·m for Ti2AlC and Ti3AlC2, respectively. The electro-tribological test was carried out using a ball-on-flat reciprocating tribometer under electrical currents of 10, 50 and 100 mA. The coefficient of friction and the electrical contact resistance were measured simultaneously in the same test. The results show that the coefficient of friction and electrical contact resistance could be related to thin-film properties such as hardness, roughness, grain size, and resistivity. These results of the electro-tribological behavior of the films provide valuable information for possible applications such as sliding electrical contacts.

La presente tesis investiga la síntesis, propiedades mecánicas, comportamiento tribológico y electrotribológico de Ti2AlC y Ti3AlC2 fases MAX en forma de películas delgadas. Las películas delgadas se obtuvieron mediante deposición de un sistema de multicapas de Titanio (Ti) - Aluminio (Al) – Carbono (C) y un posterior tratamiento térmico en vacío y atmosfera controlada. El sistema de multicapa de Ti- Al-C fue depositado mediante pulverización catódica sobre sustratos de silicio con una barrera de difusión de doble capa de SiO2 y SixNy. La estequiométrica de la película se controló a través del espesor de las monocapas individuales. Para obtener una película de 500 nm de espesor, se repitió 22 veces la secuencia de Ti-Al-C con espesores individuales de 14, 6 y 3.5 nm, respectivamente. Los resultados experimentales muestran que la fase Ti2AlC se forma a una temperatura de 700°C, mientras que la fase Ti3AlC2 se forma a 950°C. Las propiedades estructurales de las películas delgadas fueron caracterizadas mediante difracción de rayos X, microscopia Raman y espectroscopia de emisión óptica de descarga luminiscente (GD-OES). La dureza de las películas delgadas fue analizada mediante ensayos de nanoindentacion, obteniéndose valores de dureza de 11.6 y 5.3 GPa para Ti2AlC y Ti3AlC2, respectivamente. El comportamiento tribológico de las películas fue analizado bajo condiciones de deslizamiento en seco mediante el tribómetro reciprocante ball-on-flat. El contra material utilizado consiste en bolas de acero AISI 52100 de 3 mm de diámetro. Los coeficientes de fricción obtenidos están en el rango de 0.21 - 0.2 y 0.6 - 0.91 para las películas delgadas de Ti2AlC y Ti3AlC2, respectivamente. La fase Ti2AlC tiene un mejor comportamiento tribológico y esto se puede atribuir a su menor tamaño de grano, menor rugosidad superficial y mayor dureza en comparación con la fase Ti3AlC2. La resistividad eléctrica de las películas delgadas fue de 0.73 y 0.45 μΩ·m para Ti2AlC y Ti3AlC2, respectivamente. El ensayo electro-tribológico se llevó a cabo utilizando un tribómetro reciprocante ball-on-flat bajo corrientes eléctricas de 10, 50 y 100 mA. El coeficiente de fricción y la resistencia de contacto eléctrico se midieron simultáneamente en una misma prueba. Los resultados muestran que el coeficiente de fricción y la resistencia de contacto eléctrico podrían estar relacionados con las propiedades de película delgada como dureza, rugosidad, tamaño de grano y resistividad. Estos resultados del comportamiento electrotribológico de las películas proporcionan información valiosa para posibles aplicaciones como contactos eléctricos deslizantes.
Keywords: Películas delgadas; Sistemas microelectromecánicos; Tribología; https://purl.org/pe-repo/ocde/ford#1.03.00